2018
DOI: 10.1039/c8cp00151k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, properties, and formation mechanism of Mn-doped Zn2SiO4nanowires and associated heterostructures

Abstract: In this work, we have put forth a facile hydrothermal approach to synthesize an array of one-dimensional (1D) Mn-doped Zn2SiO4 nanostructures. Specifically, we have probed and correlated the effects of controllable reaction parameters such as the pH and Mn dopant concentrations with the resulting crystal structures and morphologies of the products obtained. Based upon our results, we find that careful tuning of the pH versus the Mn dopant level gives rise to opposite trends with respect to the overall size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…The oxidation state of Mn 2+ was confirmed using XPS analysis, which can be related to the 4 T 1 to 6 A 1 transitions in Mn 2+ . [46][47][48] The illumination of samples would lead to the separation of charge carriers in BiVO 4 . Since the 4 T 1 state of Mn 2+ is located below the CB of BiVO 4 , 46 it suggests favorable photogenerated electron transfer from BiVO 4 to the 4 T 1 state of Mn 2+ from where the electron will be transferred to ITO and thus will move to the extended circuit.…”
Section: Mechanism Of Charge Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation state of Mn 2+ was confirmed using XPS analysis, which can be related to the 4 T 1 to 6 A 1 transitions in Mn 2+ . [46][47][48] The illumination of samples would lead to the separation of charge carriers in BiVO 4 . Since the 4 T 1 state of Mn 2+ is located below the CB of BiVO 4 , 46 it suggests favorable photogenerated electron transfer from BiVO 4 to the 4 T 1 state of Mn 2+ from where the electron will be transferred to ITO and thus will move to the extended circuit.…”
Section: Mechanism Of Charge Transfermentioning
confidence: 99%
“…[46][47][48] The illumination of samples would lead to the separation of charge carriers in BiVO 4 . Since the 4 T 1 state of Mn 2+ is located below the CB of BiVO 4 , 46 it suggests favorable photogenerated electron transfer from BiVO 4 to the 4 T 1 state of Mn 2+ from where the electron will be transferred to ITO and thus will move to the extended circuit. Mehmood's group 49 have reported the CuInSe 2 /Mn-CdS QDs, where they suggested that the photogenerated electrons stay for a longer time in Mn the d-states and thus help in reducing the recombination of electronhole pairs in the system.…”
Section: Mechanism Of Charge Transfermentioning
confidence: 99%
“…Compared with the unlabeled CO 2 , the m/z values of CH 4 and CO produced from 13 C-labeled CO 2 molecules were 17 and 29, respectively, which confirms that the carbon source of CO and CH 4 originates from the photoreduction process of CO 2 . [58] Besides the 13 C isotope labeling experiments, 18 O isotope labeling was also conducted to confirm the half-reaction of oxidation. Shown as Figure S21, Supporting Information, the presence of 16 O 18 O and 18 O 2 in the 18 O labeling experiment verifies that O 2 originated from water oxidation.…”
Section: Photocatalytic Performance and Simulationmentioning
confidence: 99%
“…[58] Besides the 13 C isotope labeling experiments, 18 O isotope labeling was also conducted to confirm the half-reaction of oxidation. Shown as Figure S21, Supporting Information, the presence of 16 O 18 O and 18 O 2 in the 18 O labeling experiment verifies that O 2 originated from water oxidation. [59] Further CO 2 photoreduction of all prepared photocatalysts was also performed under simulated sunlight irradiation in a high pressure (10 atm) reactor system.…”
Section: Photocatalytic Performance and Simulationmentioning
confidence: 99%
See 1 more Smart Citation